The Dynamics of Care Understanding People Flows in Health and Social Care - Wolstenholme, Eric.; McKelvie, Douglas; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book describes numerous projects which shed light on some of the most persistent issues of the day in health and social care. The work demonstrates the importance of embedding the concept of flow into everyday health and social care thinking and creates insights into patient journeys through different conditions and treatments. It suggests that improving throughput across agencies is the key way to improving the performance of health treatment, whereas increasing capacity is the key way to improving the performance of social care by retaining independent living. The authors conclude that for state-provided care, balancing health and social care provision can eliminate the many stressful fire-fighting strategies hospitals have to undertake when faced with high demands, and this is a win-win scenario in terms of patients, staff and costs. Further, that there is a need for better understanding of the dynamics of population ageing, the dynamics of health conditions and the provision of better, integrated information systems. The book will be a valuable resource for practitioners, clinicians, managers and academics in health, social work, public health and public policy in many countries. In this important book Eric Wolstenholme and Douglas McKelvie bring two lifetimes of award-winning experience in applying system dynamics to improving our very clinically advanced but often dysfunctional care systems. - David F. Andersen, O'Leary Distinguished Service Professor, Emeritus, State University of New York, Albany, USA. Health and social care suffer from some persistent and serious problems which not only undermine well intended care but also impose considerable costs in many societies. This very welcome and exceptional book offers the hope of sound and sustainable solutions to many of these issues. - Kim Warren, Strategy Dynamics, London, UK.
Chapter 1. Introduction: The complexity of health and social care and wicked problems that keep re-occurring -- Chapter 2. Hospitals as Stock-Flow Systems -- Chapter 3. Hospital Delayed Transfers of Care (Delayed Discharges) -- Chapter 4. Insights into Managing Hospital Demand -- Chapter 5. Analysing Stepped Care in Mental Health -- Chapter 6. Dynamic Cost Benefit of New Mental Health Services -- Chapter 7. The Dynamic Impact of Alcohol Harm Reduction Strategies -- Chapter 8. The Dynamic Impact of New Dementia Services -- Chapter 9. Developing Workforce Strategies in Paediatrics and Child Health -- Chapter 10. Adding Population Dynamics to enhance Predictive Risk Tools -- Chapter 11. Conclusions.
Keywords: Social service; Health services administration; Medical care; Social Work; Health Care Management; Health Care